Joint replacement in patients with consequence of non-reduced hip joint fracture-dislocations - Filipenko, Volodymyr; Bondarenko, Stanislav; Khmyzov, Sergey; Zhygun, Anatoliy; Panchenko, Anastasia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Joint replacement with the consequences of non-reduced hip fracture-dislocation is complex surgical intervention. Objective: to develop a technique for hip arthroplasty and to evaluate its results in patients with consequences of hip fracture-dislocation. Methods: from 2004 to 2016 10 patients (10 joints) with the consequences of hip fracture-dislocation underwent total hip arthroplasty. The average age of the patients was 41.3 years (from 22 to 59), 5 men and 5 women. The shortening of the affected limb was on average 4.7 cm (2 to 8). In 5 patients, a reduction of the proximal femur with the external fixation device in the «pelvic floor» system was performed before joint replacement. The time of distraction and fixation in external fixation device was on the average 55 days (from 21 to 98). The acetabular component of the endoprosthesis was set in the anatomical position. Plastic defects in the acetabulum were carried out in 8 cases. Patients follow-up was from 6 month to 12 years. Results: the functional state of hip joint by the Harris score increased from 30 to 82 points. Patients with X-ray signs of instability of the endoprosthesis components were not identified. Complete restructuring of autograft was carried out in 100 % of cases. Complications related to external fixation device: 1 case — superficial soft tissue infection around the pin, 1 — fracture of the pin, 1 — early periprosthetic infection, 1 — recurrent dislocation. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the restoration of the hip joint rotation center and the length of the affected limb due to the use of the «pelvis – femur» external fixation device before joint repllacement, the reconstruction of the acetabular wall, taking into account the type of defect and the anatomical position of the endoprosthesis cup, allowed to minimize complications and obtain positive results in patients with consequences of hip fracture-dislocation.